Rethinking the Religious Turn in International Development and Global Governance: A Critical Review of Gerard Clarke - Neirna Yayah Daryati; Mohammad Taufiq Rahman; Asep Abdul Sahid (UIN Sunan Gunung Djati Bandung, 2026)
Since the post-World War II era, international development has been dominated by a modernization paradigm grounded in secular rationality, positioning it as a technocratic, growth-oriented project that neglects the religious dimension. However, global dynamics indicate a revitalization of religion in the public sphere (deprivatization), which has triggered a post-secular turn and demands the integration of religious values into development. Religion, in the context of the Global South, has proven to be an important framework for understanding poverty and social practices, as well as a source of legitimacy and moral capital. This article critically examines Gerard Clarke's work